Reversed siderophores act as antimalarial agents. - Shanzer, A (1991)
We describe here a family of biomimetic iron carriers that display high binding efficiency for ferric ions and favorable permeation properties across erythrocytic membranes. These carriers inhibit in vitro growth of Plasmodium falciparum by scavenging intracellular iron. The chemical features were realized by reproducing the iron-binding cavities of natural iron carriers (siderophores) and by systematic substitutions of their hydrophilic envelopes for more hydrophobic ones. In contrast to natural carriers, which participate in receptor-mediated iron uptake in cells and act as growth promoters, our synthetic carriers were designed to penetrate cellular membranes by diffusion, scavenge intracellular iron, and thereby act as growth inhibitors. Based on these properties we designate the compounds reversed siderophores and refer to the specific analogs of the natural ferrichrome as synthetic ferrichromes. The antimalarial activity of the synthetic ferrichromes correlated with their lipophilicity, and this antimalarial activity was averted when the chelators were applied as iron (III) complexes. The sites of synthetic ferrichrome action reside in the intraerythrocytic parasite and not in serum or on normal erythrocyte components. The agents were effective against all stages of parasite growth and against a variety of multidrug-resistant strains of P. falciparum. The most potent agent of this synthetic ferrichrome series, SF1-ileu, was not toxic to mammalian cells in culture and was 15-fold more potent and 20-fold faster acting than desferrioxamine. Taken in toto, these agents constitute a series of promising candidates for future use in malaria chemotherapy.